Efficacy of polyacrylic acid as a conditioning agent on the bond strength of self-adhesive resin cements to dental enamel - Chrisostomo, Daniela Alvim [UNESP] (2020)
Purpose: This in vitro study evaluated the effectiveness of polyacrylic acid as an acid etchant similar to phosphoric acid and its effect on the microtensile bond strength of self-adhesive resin cement to enamel. Materials and Methods: Ninety Te-Econom Plus resin blocks (11 x 4 mm) were cemented onto bovine enamel and distributed into 10 groups according to the surface treatments (no surface treatment; etching with 37% phosphoric acid; etching with 20% polyacrylic acid; etching with 37% phosphoric acid + dental adhesive, and etching with 20% polyacrylic acid + dental adhesive) and the self-adhesive resin cements used (RelyX U200 and MaxCem Elite) (n = 9). After bonding, the specimens were sectioned into sticks, subjected to thermocycling (5760 cycles, 5°C and 55°C) and microtensile bond strength testing (n = 6). Images of representative specimens were obtained using a scanning electron microscope. Enamel penetration evaluation of different surface treatments was analysed by confocal laser scanning microscopy (n = 3). Data on bond strength were subjected to 2-way ANOVA and Tukey's least significant difference test (a = 0.05). Results: Both 37% phosphoric acid and 20% polyacrylic acid yielded the same microtensile bond strength between self-adhesive resin cement and enamel, independent of the application of dental adhesives (p > 0.05). MaxCem Elite showed higher bond strength values than RelyX U200 just for the 20% polyacrylic acid group (p = 0.001). Conclusion: Acid pre-conditioning of dental enamel may influence the bond strength of self-adhesive resin cement to enamel, and 20% polyacrylic acid showed efficacy similar to that of 37% phosphoric acid.